ANALISIS PUPUK KANDANG AYAM TERHADAP EFEKTIVITAS PERTUMBUHAN KANGKUNG DARAT (Ipomoea reptans Poir.) - W. D. P., RENGGA; MALIKHANA, A.; RAYDITYA, R.; PRASETYO, R. (Majalah Ilmiah Peternakan, 2022)
Livestock waste containing untreated protein feed can affect soil, air and air pollution and be a source of toxins. Chickens and those around them will know this by free ammonia. Broiler manure waste can be used as a high nitro- gen nutrient that can be used as a fertilizer with additives needed by plants to increase soil fertility. The purpose of this study was to create and analyze nitrogen-rich fertilizers from broiler manure that affect plant growth or fertili- zer efficiency on productivity, growth efficiency of water spinach (Ipomoea reptans Poir.). As a result, poultry com- post contained water (63.38), nitrogen (N) (2.400%), P2O5 (3.914%), and K2O (1.113%), so N levels, P, K (7.447%). It was performed for 14 days with 3 different nutritional sources. The most effective treatment for growing aquatic spinach was the use of a combination of soil and fertilizer applied in specific proportions to obtain stem height (23.55 cm), leaf number (6.2 leaves) and leaf width (3.1 cm). Results were better compared to other treatments.